2006
DOI: 10.1242/jeb.02304
|View full text |Cite
|
Sign up to set email alerts
|

The influence of collagen fiber orientation and other histocompositional characteristics on the mechanical properties of equine cortical bone

Abstract: In cortical bone, regional variations in predominant collagen fiber orientation (CFO) and other histocompositional (material) characteristics may represent biomechanically important adaptations related to specific strain modes of tension, compression, or shear. For example, regions habitually loaded in compression have relatively more oblique-to-transverse collagen compared to regions loaded in tension, which have relatively more longitudinal collagen (Carando et al., 1991;Kalmey and Lovejoy, 2002;Mason et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 113 publications
(215 reference statements)
0
74
0
Order By: Relevance
“…However, our finding that the osteonal order in the investigated horse radius is independent of anatomic location does not support this hypothesis. The second investigated bone, the metacarpal of horses, has been shown to be loaded primarily in torsion (Skedros et al, 2006;Skedros et al, 2007). In our analysis, the metacarpal bone displays higher order at the lateral compared with the cranial location.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…However, our finding that the osteonal order in the investigated horse radius is independent of anatomic location does not support this hypothesis. The second investigated bone, the metacarpal of horses, has been shown to be loaded primarily in torsion (Skedros et al, 2006;Skedros et al, 2007). In our analysis, the metacarpal bone displays higher order at the lateral compared with the cranial location.…”
Section: Discussionmentioning
confidence: 72%
“…However, this observed anisotropy of the ACFs in the metacarpal bones cannot be explained based on purely torsional loading. It has been reported that some third metacarpals have a loading history of combined torsion with bending (Skedros et al, 2006), which would account for loss of rotational asymmetry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that under variable locomotor conditions a curved bone will not see remarkably less varied principal strain orientations than a straight bone, but the curved bone will restrict the ratio of tension to compression to within a more predictable range for any given footfall, whereas a straight bone will experience more variable tension-to-compression ratios. In this case, a critical factor for preventing failure during non-steady activities may be the specific bone microstructure and collagen fiber orientation in the cortices of straight bones compared with curved bones (Skedros et al, 2006), which is a level of detail not examined in our study.…”
Section: Effect Of Bone Curvature On the Variability Of Strain Pattermentioning
confidence: 97%
“…As mentioned in previous studies, tissue-level properties can be divided into the inorganic mineral phase (e.g., hydroxyapatite), which determines tissue stiffness and strength, 80,81 and the organic bone matrix, which plays a key role in energy absorption, 82,83 It has been suggested that the networks of collagen, one of the major components of bone matrix, could affect the energy dissipation between the yield point and fracture point in bone tissue. [84][85][86] Collagen fiber orientation (CFO) has been measured by circularly polarized light microscopes as one parameter to represent the collagen network and to predict post-yield energy of bone tissue. 84 Hence, the post-yield behavior revealed by ERT rats' bone tissue could partially stem from a highly organized collagen fiber network.…”
Section: Effects On Tissue-level (Material) Propertiesmentioning
confidence: 99%